Changing or validating physician opioid prescribing behaviors through audit and feedback and academic detailing interventions in primary care - Celia Laur; Natasha Kithulegoda; Nicola McCleary; Emily Nicholas Angl; Michael Strange; Barbara Sklar; Thivja Sribaskaran; Gail Dobell; Sharon Gushue; Jonathan M. C. Lam; Lindsay Bevan; Victoria Burton; et al. (Implementation Research and Practice)
Background In Ontario, Canada, province-wide initiatives supporting safer opioid prescribing in primary care include voluntary audit and feedback reports and academic detailing. In this process evaluation, we aimed to determine the fidelity of delivery and receipt of the interventions, the observed change strategies used by physicians, potential mechanisms of action, and how complementary the initiatives can be to each other. Method Semi-structured interviews were conducted with academic detailers and with physicians who received both interventions. Academic detailer interviews were coded using the Behavior Change Technique Taxonomy; physician interviews were coded to the Theoretical Domain Framework. Change strategies were summarized based on academic detailer intentions and physician-reported practice changes. Potential mechanisms of action were identified using the Theories and Techniques Tool and the literature. Patient partners informed the interpretation of results through ongoing group discussions of preliminary findings. Results Interviews were conducted with eight academic detailers and 12 physicians. Change strategies described by academic detailers to support physicians’ opioid prescribing included problem solving , instructions on how to perform the behavior , adding objects to the environment , credible source , shaping knowledge , and social support. Physicians mentioned that academic detailing validated current opioid practices or increased their belief about capabilities and their intentions , mediated by increased skills and the impact of environmental context and resources . Potential mechanisms of action included behavioral regulation , behavioral cueing , and general attitudes/beliefs. On its own, receiving the audit and feedback report did not lead to changes in beliefs about prescribing practices; however, for some physicians, it provided validation and reassurance. Physicians saw unrealized potential for complementarity. Conclusions New interventions are often implemented in a complex ecosystem with other competing interventions. In this study, we show how examining the fidelity of the intervention from initial design through to delivery can identify opportunities for potential optimization.